The Implementation the Pegel’s Classification to Forecast Rice Prices Based on Quality at The Milling Level: Forecast Rice Prices - Ramadhani, Sausan (International Journal of Mathematics, Statistics, and Computing, 2025)
Rice is the primary food of the Indonesian people and plays an important role in various aspects. In fact, the increase rice prices in Indonesia has occurred from 2014 until now. The burden on society continues to occur when the discourse of increasing PPN issue by 12% in 2025 is delivered by the government. Business actors, especially food and consumers, are very influenced by this policy. Against this background, this study analyzes the average prediction of rice prices at the milling level according to quality. The Pegel’s Classification is the technique employed in this research. The data used in this study from Badan Pusat Statistik (BPS). The predicted price of premium or medium rice less than IDR 14,000 with a difference of no more than IDR 700 for each quality. February 2025 is the predicted highest average price for rice for each quality, with a decrease in March. Pegel’s B-2 model is an best effective model because it has a Mean Absolute Percentage Error (MAPE) value of 2.02%.